Additions to the Marine Mastogloia (Bacillariophyceae) from Cuban Coasts; Remarks on Misidentified Taxa - David Alfaro Siqueiros Beltrones; Erisbel Echevarría Herrera; Francisco Omar López-Fuerte (Diversity)
During a floristic inspection of sediment samples from Playa Las Gaviotas, 69 specific and infra-specific taxa of Mastogloia were identified in the diatom taxocenosis, including 42 unrecorded taxa for the Cuban coasts. These are added to the 59 Mastogloia taxa previously listed. In this way, currently, the 101 Mastogloia comprised in the benthic diatom associations of the Cuban coast constitute the highest number of taxa ever recorded in similar floristic studies, which also indicates their tropical affinity. Furthermore, observations are made on misidentified taxa such as Mastogloia (Orthoneis) aspera, M. asperuloides, M. (Orthoneis) clevei, M. floridensis, M. latecostata, M. laterorostrata, M. ovata, M. sigillata, M. pseudolatecostata, and others.